2003
DOI: 10.1021/ic026008m
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modulation of Cu(I) and Cu(II) Complexes of Sterically Hindered Tripyridine Ligands by the Bridgehead Alkyl Groups

Abstract: Structures of Cu(I) and Cu(II) complexes of sterically hindered tripyridine ligands RL = tris(6-methyl-2-pyridyl)methane (HL), 1,1,1-tris(6-methyl-2-pyridyl)ethane (MeL), and 1,1,1-tris(6-methyl-2-pyridyl)propane (EtL), [Cu(RL)(MeCN)]PF(6) (1-3), [Cu(RL)(SO(4))] (4-6), and [Cu(RL)(NO(3))(2)] (7-9), have been explored in the solid state and in solution to gain some insights into modulation of the copper coordination structures by bridgehead alkyl groups (CH, CMe, and CEt). The crystal structures of 1-9 show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…[64][65][66] We found that copper complexes with sterically hindered tripyridine ligands can be structurally modulated by introducing an alkyl group at the bridgehead position of the ligand. 67 We prepared three sterically hindered tripyridine ligands: tris-(6-methyl-2-pyridyl)methane (H6M3t), 68 1,1,1-tris(6-methyl-2-pyridyl)ethane (Me6M3t), 67 and 1,1,1-tris(6-methyl-2-pyridyl)propane (Et6M3t). 67 The chemical structures of H6M3t, Me6M3t, and Et6M3t are shown in Chart 4.…”
Section: Reversible O 2 -Binding Greatly Improved By Structural Modulmentioning
confidence: 99%
See 4 more Smart Citations
“…[64][65][66] We found that copper complexes with sterically hindered tripyridine ligands can be structurally modulated by introducing an alkyl group at the bridgehead position of the ligand. 67 We prepared three sterically hindered tripyridine ligands: tris-(6-methyl-2-pyridyl)methane (H6M3t), 68 1,1,1-tris(6-methyl-2-pyridyl)ethane (Me6M3t), 67 and 1,1,1-tris(6-methyl-2-pyridyl)propane (Et6M3t). 67 The chemical structures of H6M3t, Me6M3t, and Et6M3t are shown in Chart 4.…”
Section: Reversible O 2 -Binding Greatly Improved By Structural Modulmentioning
confidence: 99%
“…67 We prepared three sterically hindered tripyridine ligands: tris-(6-methyl-2-pyridyl)methane (H6M3t), 68 1,1,1-tris(6-methyl-2-pyridyl)ethane (Me6M3t), 67 and 1,1,1-tris(6-methyl-2-pyridyl)propane (Et6M3t). 67 The chemical structures of H6M3t, Me6M3t, and Et6M3t are shown in Chart 4. Crystal structures of Cu I complexes with these ligands are shown in Fig.…”
Section: Reversible O 2 -Binding Greatly Improved By Structural Modulmentioning
confidence: 99%
See 3 more Smart Citations